Aspek Biologi Hiu (Rhizoprionodon taylori) Hasil Tangkapan di Perairan WPP 718 Indonesia - Firdha Iresta Wardani (JURNAL ENGGANO, 2024)
Shark fishing activity is an economically important activity because sharks are the target fish for export purposes. Sharks are consumed by their fins dan flesh. The relatively high demand demand for shark exports with low reproduction characteristics makes sharks more vulnerable to population threats. In managing sharks fishery, biological aspect are supporting things as a reference for management actions. The study aims to describe the fishing characteristic of shark (Rhizoprionodon taylori), length to weight relationship, length distribution, and sex ratio. Sharks are more susceptible to population risks because of the relatively high demand for shark exports and their lack of reporting characteristics. Biology plays a supportive role in shark management by serving as a point of reference for management efforts. This study attempts to describe the length-to-weight relationship, length distribution, and sex ratio of the shark (Rhizoprionodon taylori) as they relate to fishing. The collection and capture of biological data took place between February and August of 2022. TPI Dermaga Barat Pelabuhan Perikanan Samedera Nizam Zachman (PPSNZ), Muara Baru, North Jakarta, is where the fish used for the fish samples were landed. Biology fish samples data were weighed,fork length and  sex. At sizes ranging from 38.6 cm to 43 cm and a negative allometric development trend, the long shark (Rhizopodon taylori) predominates. 94% of the sampled fish were female, showing that female fish predominate in the catch. It will decrease fish stocks that can reproduce, which will result in lower recruitment in the waters, if the capture is consistently dominated by female fish. Keywords : Long Weight Relationship, Shark Catching, Sex Ratio, WPP 718